Exceptional combination of large magnetostriction, low hysteresis and wide working temperature range in (1-x)TbFe2-xDyCo2 alloys. (November 2021) - Zhao, Hui; Ji, Yuanchao; Ma, Tianyu; Fang, Minxia; Hao, Yanshuang; Yang, Tianzi; Zhou, Chao; Yang, Sen; Ren, Xiaobing
Abstract: Magnetostrictive materials with large magnetostriction, low hysteresis and wide working temperature range are desired for applications, but rarely obtained so far. In this work, we report a surprising finding in (1-x)TbFe2 -xDyCo2 alloys: the composition of x = 0.5 exhibits a low hysteretic magnetostriction, λ ||, max ∼2066 ppm, which is 1.59 times as large as that of the commercial giant magnetostrictive alloy of Terfenol-D, λ ||, max ∼1298 ppm. Moreover, its temperature range for λ || >1298 ppm is even larger than 240 K, and another working temperature window for λ || >1000 ppm is from 40 K to 324 K, which can cover a large temperature fluctuation in space environments (e.g. 120-290 K in Mars). The established phase diagram of (1-x)TbFe2 -xDyCo2 by systematic studies of magnetic susceptibility, X-ray diffraction and convergent-beam electron diffraction results, shows an emergence of morphotropic phase boundary (MPB) between rhombohedral (R) and orthorhombic (O) ferromagnetic phases, which is different from the MPB between R and T (tetragonal) phases in (1-y)TbFe2 -yDyFe2 . We reveal that the exceptional combination of giant magnetostriction, low hysteresis and wide working temperature range is caused by this R-O MPB. The comparison between R-O MPB and R-T MPB further shows the O phase plays a vital role in the property enhancement of R-O MPB composition. Our work indicates the construction of R-O MPB may provide a new way to find high-performance magnetostrictive materials. Graphical abstract: Image, graphical abstract